Trade and smuggling between Pará, the Franco-Brazilian Contested and French Guiana in the 1870s - Paz, Adalberto (Revista de História, 2021)
Since the end of the 17th century, Portugal and then Brazil disputed with France what would be the limit of their possessions in northern South America, in a region corresponding to about half of the current state of Amapá. In 1841, Brazilian and French authorities agreed that neither country would have governance over the so-called Franco-Brazilian Contest. As a result, that area became a haven for various communities of fugitives, maroons and villages that managed themselves autonomously. Thus, this article analyzes the commercial exchanges established between the inhabitants of the province of Pará, the contested area and the French Guiana, investigating their strategies to circumvent the inspection of the Brazilian authorities, and their attempts to contain or at least control the circulation and trade networks by along the Atlantic coast in the northern Amazon.